DESCRIPTION DES HABITUDES ALIMENTAIRES DU CHINCHARD TRACHURUS TRACHURUS DE L’ATLANTIQUE NORD MAROCAIN - Shawket, Nizar; Youssir, Sanaa; El Halouani, Hassan; Elmadhi, Youssef; El Kharrim, Khadija; Belghyti, Driss (European Scientific Journal, ESJ, 2015)
The study relates to the description of the diet of horse mackerel “Trachurus trachurus” of the northern Moroccan Atlantic ocean. The fishes were captured in July 2010 between Larache and Sidi Ifni. The 120 individuals sampled were between 15 and 41cm and weighed between 30 and 484g. The nutritional composition shows that the Trachurus trachurus is a carnivore species. Four major taxonomic groups of prey have been identified (crustaceans, mollusks, echinoderms and fish) .The diet varies with the size of individuals who tend to ingest prey to larger and larger as their size increases. The emptiness coefficient is within 27.5%. The proportion of empty stomachs varied by size classes.